A Method of Locating the Dehiscence during Middle Fossa Approach for Superior Semicircular Canal Dehiscence Surgery - Beckett, Joel S.; Chung, Lawrance K.; Lagman, Carlito; Voth, Brittany L.; Jacky Chen, Cheng Hao; Gaonkar, Bilwaj; Gopen, Quinton; Yang, Isaac (Journal of Neurological Surgery Part B: Skull Base, 2017)
Objectives Superior semicircular canal dehiscence (SSCD) results from a defect in the middle cranial fossa floor. One challenge during SSCD repair is the lack of a consistent landmark. This study proposes a reference point above the external auditory canal at the level of the zygoma as the inferior craniectomy edge during surgery.Design This is a retrospective review of patients with SSCD.Setting/Participants A total of 72 cases of SSCD in 60 patients were repaired via a middle fossa approach at a single institution.Main Outcome Measures The distance from the proposed reference point to the dehiscence was statistically analyzed using Shapiro–Wilk's goodness-of-fit test and Student's t-test.Results Average distance for all patients was 28.84 ± 2.22 mm (range: 22.96–33.43). Average distance for females was 29.08 mm (range: 24.56–33.43) versus 28.26 mm (range: 22.96–32.36) for males. There was no difference in distance by sex (p = 0.174). The distance measurements followed a normal distribution with 95% of the patients between 24.49 and 33.10 mm.Conclusion This study analyzed a potential reference point during a middle fossa approach for SSCD surgery. The distance from this reference point to the SSCD was found to be consistent and may serve as a readily identifiable landmark in localizing the dehiscence.
Keywords: superior semicircular canal dehiscence; syndrome; distance; measurement